In vitro and in vivo anti-inflammatory properties of imine resveratrol analogues. Issue 17 (15th September 2018) - Zimmermann-Franco, Danielle Cristina; Esteves, Bruna; Lacerda, Leticia Moroni; Souza, Isabela de Oliveira; Santos, Juliana Alves dos; Pinto, Nícolas de Castro Campos; Scio, Elita; da Silva, Adilson David; Macedo, Gilson Costa
Graphical abstract: Highlights: Imines resveratrol analogues are less cytotoxicity than thioimines and hydrazones. The imines are more effective than resveratrol on DPPH scavenger. The imines reduce pro-inflammatory mediators production in vitro. The imines decrease lymphocyte proliferation and costimulatory molecules. The imines control edema formation, cytokines and myeloperoxidase production in vivo. Abstract: Resveratrol is a natural polyphenol found mainly on red grapes and in red wine, pointed as an important anti-inflammatory/immunomodulatory molecule. However, its bioavailability problems have limited its use encouraging the search for new alternatives agents. Thus, in this study, we synthetize 12 resveratrol analogues (6 imines, 1 thioimine and 5 hydrazones) and investigated its cytotoxicity, antioxidant activity and in vitro anti-inflammatory/immunomodulatory properties. The most promising compounds were also evaluated in vivo . The results showed that imines presented less cytotoxicity, were more effective than resveratrol on DPPH scavenger and exhibited an anti-inflammatory profile. Among them, the imines with a radical in the para position, on the ring B, not engaged in an intramolecular hydrogen-interaction, showed more prominent anti-inflammatory activity modulating, in vivo, the edema formation, the inflammatory infiltration and cytokine levels. An immunomodulatory activity also was observed in these molecules. Thus, our results suggest that imines with these characteristics presents potential to control inflammatory disorders.